Systematic review of the scientific evidence on ethylene oxide as a human carcinogen. (1st September 2022) - Lynch, Heather N.; Kozal, Jordan S.; Russell, Anthony J.; Thompson, William J.; Divis, Haley R.; Freid, Rachel D.; Calabrese, Edward J.; Mundt, Kenneth A.
Abstract: Ethylene oxide is a highly reactive chemical primarily used as an intermediate in chemical production and as a sterilant of medical equipment and food products; it also is produced endogenously as a result of physiological processes. We conducted a systematic review of the potential carcinogenicity of inhaled ethylene oxide in humans using methods that adhere to PRIMSA guidelines and that incorporate aspects from the Institute of Medicine (IOM) (now the National Academy of Medicine) as well as several US Environmental Protection Agency (EPA) frameworks for systematic reviews. After a comprehensive literature search and selection process, study quality was evaluated following a method adapted from the EPA Toxic Substances Control Act (TSCA) framework. The literature screening and selection process identified 24 primary studies in animals or humans and more than 50 mechanistic studies. Integrating epidemiological, animal, and mechanistic literature on ethylene oxide and cancer according to the IOM framework yielded classifications of suggestive evidence of no association between ethylene oxide and stomach cancer, breast cancer and lymphohematopoietic malignancies at human relevant exposures. However, we acknowledge that there is additional uncertainty in the classification for lymphohematopoietic malignancies owing to a paucity of evidence for specific types of these tumors, each of which is a distinct disease entity of possibly unique etiology. Highlights: Evaluated quality and integrated all lines of evidence on ethylene oxide and cancer. Hybrid systematic review method leveraged strengths of multiple frameworks. Ethylene oxide has a genotoxic mode of action but evidence demonstrates a threshold. Risk deficits in less-exposed workers cause spuriously high relative risk estimates. Suggestive evidence of no association for all cancers at current human exposures.